PP23 The role of physical disease in the development of resilience and resilient outcomes: a systematic review of resilience definitions, study methods and findings. (2nd September 2014) - Johnston, M; Black, C; Burton, C; Crilly, M; Elliot, A; Iversen, L; Porteous, T
Abstract : Background: Resilience describes the process of effectively managing or adapting to trauma. Physical disease and its association with resilience is a relatively new area of study. There is no consensus as to the definition and measurement of resilience in the context of physical disease and no consistency in the approaches taken to study it. The aim was to carry out a systematic review of studies examining physical disease and its relationship to resilience in order to summarise the range of definitions of physical disease resilience and the approaches taken to study it. Methods: Medline, Embase, PsychInfo, PubMed and the Cochrane database were searched from database inception to March 2013. Inclusion criteria were: (1) Resilience is measured or predicted; (2) Physical disease is a predictor of resilience or an adversity causing resilience; (3) Quantitative empirical research; (4) Adult populations. Screening and selection of papers and data extraction was carried out independently by two reviewers with disagreements resolved by a third reviewer. Papers were quality assessed with this being used to inform interpretation of the findings. Study characteristics, resilience definitions, methods and findings were extracted. Results were combined using a narrative technique Results: Of 2280 articles, 12 met the inclusion criteria. Nine were of acceptable or high quality. Studies varied considerably. However, the author definitions of resilience were similar across studies, relating to the concept of maintaining healthy levels of functioning or returning to normal function following adversity. There was some agreement that resilience is a dynamic process and not a personality trait and that an adversity leading to resilience should be identified when studying resilience. Studies either assessed resilience based upon observed outcomes (e.g. quality of life) or via resilience measurement scales. The disease of interest was statistically significantly associated with the resilient outcome in four papers although the direction of association varied. A range of demographic, social and psychological factors were also associated with resilience in those with physical disease. Conclusion: Further work is required to improve the evidence base regarding the definition and measurement of physical disease resilience. Our focus was upon studies in which resilience was an outcome variable in those with physical disease. Our future work will focus upon summarising studies where resilience is a predictor variable for physical disease outcomes. This review is important with the rising prevalence of chronic disease as our population ages. By improving the consistency of definitions and approaches taken when studying physical disease resilience it may be feasible to develop approaches to promote resilience in order to reduce the burden of disease.